Perbandingan Hukum Jaminan Fidusia Antara Indonesia dan Belanda Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Christy, Lisya Jatasiri; Basyarahil, Ramzy Muhammad (Magister Kenotariatan Universitas Surabaya, 2025)
The Constititional Court Decision Number 18/PUU-XVII/2019 significantly changed the execution mechanism of fiduciary guarantess in Indonesia. Previously, creditors holding a Fiduciary Guarantee Certificate could directly execute the guarantee without a court ruling. Nevertheless, after the ruling, enforcement may proceed solely when the guaranteed asset is handed over willingly as a result of the debtor’s acceptance of their noncompliance. Otherwise, the creditor must seek court approval. This shift creates legal uncertainty and weakens the creditor’s legal standing. This paper addresses two main issues: (1) What are the impacts of the Constitutional Court Decision Number 18/PUU-XVII/2019 in conjuction with Decision Number 2/PUU-XIX/2021 on creditor protection in fiduciary guarantees ? And (2) How does the post-decision guarantee system in Indonesia compare to the Dutch legal system, particularly in terms of creditor protection and execution procedures? The study examnines how the Constitutional Court’s rulling affects vreditors’ right while also considering the Dutch non-possessory (silent pledge) as a potential reference for legal reform. Since 1992, the Netherlands has replaced fiduciary guarantees with the silent pledge, a system that ensures creditor priority without requiring court involvement and offers stronger legal certainty. This model may serve as a viable solution to improve the fairness and effectiveness of fiduciary guarantee enforcement in Indonesia.